Combined effects of mixing ratios and tree size: how do mixed forests respond to climate and drought events? - Wang, Xiaoxia; He, Lulu; Ullah, Haseen; Shi, Xiaopeng; Hou, Jingyu; Liu, Yadong; Liu, Yang; Xue, Liu; He, Baohua; Duan, Jie (Frontiers in Plant Science, 2024)
Although the relationship between biodiversity and ecosystem functionality (BEF) has been studied comprehensively, how the mixing ratio of tree species in mixed forests affects the response of trees to climate and drought remains an unexplored and rather unknown question. Hence, we established treering chronologies for Pinus tabuliformis Carr. (P) and Quercus variabilis Blume. (Q) mixed forests with different mixing ratios. In the temperate region of China, we investigated three mixing ratios: 90% P and 10% Q (P9Q1), 60% P and 40% Q (P6Q4), and 20% P and 80% Q (P2Q8). We collected tree ring samples using three tree size categories: dominant, intermediate, and suppressed trees. We explored the climate sensitivity of these trees and their drought tolerance indices-resilience (Rs), resistance (Rt), and recovery (Rc) under two drought conditions: short-term drought (1993 drought) and long-term drought (1999-2015 drought). P6Q4 made P. tabuliformis more sensitive to the Palmer drought severity index (PDSI) from the previous year than the other two ratios. The effect of the mixing ratio on drought response was insignificant under short-term drought in both tree species. Rt, Rc, and Rs of P. tabuliformis decreased with an increasing Q. variabilis:P. tabuliformis ratio in longterm drought. Rt, Rc, and Rs of Q. variabilis were the highest in P6Q4. The sensitivity of trees to PDSI varied among classes and was influenced by the mixing ratio. Dominant trees were most sensitive to PDSI in P6Q4 and P2Q8, whereas intermediate and suppressed trees were more sensitive to PDSI in P9Q1. The impact of tree size on drought tolerance indices varied according to drought